If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6=a+4/6
We move all terms to the left:
6-(a+4/6)=0
We add all the numbers together, and all the variables
-(+a+4/6)+6=0
We get rid of parentheses
-a+6-4/6=0
We multiply all the terms by the denominator
-a*6-4+6*6=0
We add all the numbers together, and all the variables
-a*6+32=0
Wy multiply elements
-6a+32=0
We move all terms containing a to the left, all other terms to the right
-6a=-32
a=-32/-6
a=5+1/3
| (7n+9)=–(5n+7) | | -6=-16+-3n | | 5+5x= 5x–4 | | 11-8x=45 | | 1.8=-w | | 15x+6=8x+76 | | (x+4)(x²-x-2)=0 | | 4/6x=42 | | 0.4(y+12)=1.2( | | (b+3)8=24 | | 21=-7(2x1) | | x(4x)(x+5)=0 | | 16^(3k+1)=1 | | 2x-45=-4x+45 | | x(4x)(x+5)=288 | | 3a+1/a=21 | | (3x-4)/(5x-16)=15/21 | | -6x+36=60 | | x+x/2−4=x/4 | | 3(15-x)=24 | | X²-5y²-1=0 | | 437.08=190+.87x | | 63x-147=28x+302 | | 3(10-x)=23 | | 3x+10+x+10+2x+10=180 | | -4x+48=88 | | 5(v-2)=-2(7-3v)-4 | | 129=2x+5(2x–3) | | 406.92=180+.93x | | m/2-13=-8 | | 23x–1=32 | | -3x-9=2x-8 |